CD147 Targeting by AC-73 Induces Autophagy and Reduces Intestinal Fibrosis Associated with TNBS Chronic Colitis. (14th July 2022) - Butera, Alessia; Quaranta, Maria Teresa; Crippa, Luca; Spinello, Isabella; Saulle, Ernestina; Di Carlo, Nazzareno; Campanile, Doriana; Boirivant, Monica; Labbaye, Catherine
Abstract: Background and Aims: Intestinal fibrosis is a common complication of inflammatory bowel diseases. Medical treatment of intestinal fibrosis is an unmet therapeutic need. CD147 overexpression can induce myofibroblast differentiation associated with extracellular matrix deposition, favouring the development of fibrosis. To understand whether CD147 may promote intestinal fibrosis, we analysed its expression and blocked its function by using its specific inhibitor AC-73 [3-2-[([1, 1'-biphenyl]-4-ylmethyl) amino]-1-hydroxyethyl phenol] in the murine TNBS [trinitrobenzenesulfonic acid]-chronic colitis model associated with intestinal fibrosis. Methods: TNBS chronic colitis was induced by weekly intrarectal administration of escalating doses of TNBS. Ethanol-treated and untreated mice were used as controls. Separated groups of TNBS, ethanol-treated or untreated mice received AC-73 or vehicle administered intraperitoneally from day 21 to day 49. At day 49, mice were killed, and colons collected for histological analysis, protein and RNA extraction. CD147, α-SMA and activated TGF-β1 protein levels, CD147/ERK/STAT3 signalling pathway and autophagy were assessed by Western blot, collagen and inflammatory/fibrogenic cytokines mRNA tissue content by quantitative PCR. Results: In mice with chronic TNBS colitis, CD147 protein level increased during fibrosis development in colonic tissue, as compared to control mice. CD147 inhibition by AC-73 treatment reduced intestinal fibrosis, collagen and cytokine mRNA tissue content, without significant modulation of activated TGF-β1 protein tissue content. AC-73 inhibited CD147/ERK1/2 and STAT3 signalling pathway activation and induced autophagy. Conclusions: CD147 is a potential new target for controlling intestinal fibrosis and its inhibitor, AC-73, might represent a potential new anti-fibrotic therapeutic option in IBD.